Correlation among the BRAF Gene Mutation Status, Clinicopathological Features of Primary Tumour, and Lymph Node Metastasizing of Papillary Thyroid Carcinoma - Lukas, J.; Drabek, J.; Dudesek, B.; Vazan, P.; Stranska, J.; Jancik, S.; Mackova, M.; Syrucek, M.; Lukas, D.; Duskova, J.; Dundr, P.; Hintnausova, B.; Jiskra, J. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Background: Papillary thyroid carcinoma (PTC) is the most common malignant thyroid tumour. A common mutation of papillary thyroid carcinoma (PTC) is the somatic mutation of the BRAFV600E gene.Aim: The aim was to 1) determine the association of lymph node metastases of PTC with the BRAF gene mutation of primary tumour; 2) evaluate association of the BRAF mutation in the primary tumour with clinicopathological parameters; 3) examine the extent of genetic heterogeneity by monitoring the BRAF mutation in multicentric tumours. Subjects and methods: Retrospective analysis of the BRAFV600E mutation in PTC and PTC neck lymph node metastases in 156 patients operated from 2003 to 2012 in Prague and Zlín, the Czech Republic, using a qPCR assay. The results were correlated with clinicopathological factors.Results: DNA was successfully extracted from 137 samples. The BRAFV600E mutation was detected in 78 cases (56.9%). The patients with BRAF p.Val600Glu mutation of primary tumour had only non-significantly higher risk of cervical lymph node metastases [OR=2.39 (95%) CI 1.00–5.75, p=0.052]. In the classic papillary variant, the BRAFV600E mutation was found significantly more often than in other PTC subtypes (p=0.022). We did not confirm any significant association between the BRAFV600E mutation and other clinicopathological findings.Conclusion: Except for the higher prevalence in papillary variant of PTC, BRAF p.Val600Glu mutation was not associated with other prognostic clinicopathological factors of PTC. BRAF mutation cannot be regarded as a reliable marker of node metastases in patients with PTC.
Keywords: papillary carcinoma; BRAFV600E mutation; clinical and pathological parameters; neck node metastases